Dental hygiene students' participation as subjects in a randomized controlled trial: A full evidence‐based dentistry experience. Issue 1 (7th September 2022) - Chambers, David W.
Abstract: Purpose: Demonstrate that dental hygiene students' participation in a randomized controlled trial comparing the plaque‐removing capability of two toothbrushes provides a fuller understanding of the factors affecting the potential application of research to practice. Methods: All students ( N = 18) in a baccalaureate dental hygiene class were engaged in the design of a randomized controlled trial using the Consolidated Standards of Reporting Trials (CONSORT) standard and then participated as subjects in a staggered, repeated measures trial using plaque removal as the dependent variable and brush type, brush head wear, and time in study as independent variables. A debriefing of student participation and lessons learned from analyzing the results was conducted. Results: The study found statistically significant differences in plaque removal capability. Brush type accounted for only 4% of the variance, while measures of brush head wear were inconsistent, and time in the study ("experimental fatigue") accounted for the most variance (9%). Students recognized and confirmed by their personal experiences that research that fails to focus on variance can create an overly optimistic impression of research effectiveness. There was strong agreement that subjects/patients vary widely and that performance depends on multiple factors. Conclusions: Dental hygiene students who participated as subjects in a randomized controlled trial comparing toothbrushes for plaque removal capacity felt that full analysis to account for all sources of variance and estimate the magnitude of measures of effect add to the value of reported research. Variation across patients is important in practice, if often overlooked as an "error" in the literature.